2015
DOI: 10.5014/ajot.2015.016022
|View full text |Cite
|
Sign up to set email alerts
|

Hand Strength, Handwriting, and Functional Skills in Children With Autism

Abstract: This study provides evidence that grip and pinch strength are important components in developing pencil control, handwriting legibility, and independence with functional fine motor tasks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 34 publications
(66 reference statements)
1
17
1
Order By: Relevance
“…This result was in contrary to a previous study conducted in children with JIA to measure the limitation of physical activity in relation to HGS [6]. In Alaniz et al [28] study, they used a self-assessment questionnaire and observed a significant correlation between wrist-related symptoms and problems at school. However our results were in agreement with similar studies in adult patients with RA [29] and in children with different disability [28].…”
Section: Discussioncontrasting
confidence: 63%
“…This result was in contrary to a previous study conducted in children with JIA to measure the limitation of physical activity in relation to HGS [6]. In Alaniz et al [28] study, they used a self-assessment questionnaire and observed a significant correlation between wrist-related symptoms and problems at school. However our results were in agreement with similar studies in adult patients with RA [29] and in children with different disability [28].…”
Section: Discussioncontrasting
confidence: 63%
“…In childhood, grip strength and finger dexterity facilitate key academic tasks, such as handwriting. Indeed, grip strength was found to be correlated with pencil control and handwriting legibility in children with ASD (Alaniz, Galit, Necesito & Rosario, ). Poor handwriting may have detrimental effects on tasks like taking notes and completing math problems, creating a lasting impact on academic performance.…”
Section: Introductionmentioning
confidence: 99%
“…3 The strength of intrinsic muscles of digits and thumb contribute to important functional hand activities, especially for those requiring dexterous hand movements, such as handwriting. 4,5 Moreover, measuring isolated hand intrinsic muscle strength can evaluate or monitor the progression or resolution of certain hand pathologies, hand therapy intervention effects, and research outcomes with greater specificity. For example, the first dorsal interosseous (FDI) and abductor digiti minimi are innervated by ulnar nerve, and thus the strength of these muscles may be clinical indicators to understand hand function and recovery in patients with ulnar nerve injuries.…”
Section: Introductionmentioning
confidence: 99%
“…Decreased hand intrinsic strength may be experienced in youth with Charcot-Marie-Tooth disease, brachioplexopathies, juvenile rheumatoid arthritis, and hand overuse 1218 and may be associated with limitations in self-care skills (eg, opening a snack box) and academic performance (eg, handwriting). 4 Many with hand dysfunction require surgeries such as tendon transfers or lengthening and nerve repair, 19,20 hand therapy after acute injuries and operation, or developmental rehabilitation for hand use in those born with disabilities. The use of a responsive psychometrically sound tool with normative reference values can assist in evaluating the success of these therapy and surgical interventions.…”
Section: Introductionmentioning
confidence: 99%